Evolutionary anatomy of the Neandertal ulna and radius in the light of the new El Sidrón sample. Issue 106 (May 2017) - Pérez-Criado, Laura; Rosas, Antonio
Abstract: This paper aims to improve our understanding of the phylogenetic trait polarity related to hominin forearm evolution, in particular those traits traditionally defined as "Neandertal features." To this aim, twelve adult and adolescent fragmented forelimb elements (including ulnae and radii) of Homo neanderthalensis recovered from the site of El Sidrón (Asturias, Spain) were examined comparatively using three-dimensional geometric and traditional morphometrics. Mean centroid size and shape comparisons, principal components analysis, and phylogenetic signal analysis were undertaken. Our investigations revealed that the proximal region of the ulna discriminated best between Neandertals and modern humans, with fewer taxonomically-informative features in the distal ulna and radius. Compared to modern humans, the divergent features in the Neandertal ulna are an increase in olecranon breadth (a derived trait), lower coronoid length (primitive), and anterior orientation of the trochlear notch (primitive). In the Neandertal radius, we observe a larger neck length (primitive), medial orientation of the radial tubercle (secondarily primitive), and a curved diaphysis (secondarily primitive). Anatomically, we identified three units of evolutionary change: 1) the olecranon and its fossa, 2) the coronoid–radius neck complex, and 3) the tubercle and radial diaphysis. Based on our data, forearm evolution followed a mosaic pattern in which some features were inherited from a pre- Homo ancestor, others originated in some post- ergaster and pre- antecessor populations, and other characters emerged in the specific Homo sapiens and H. neanderthalensis lineages, sometimes appearing as secondarily primitive. Future investigations might consider the diverse phylogenetic origin of apomorphies while at the same time seeking to elucidate their functional meaning.